2021
DOI: 10.1177/0160449x211003213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Mexican Consulate Network in Assisting Migrant Labor Claims across the U.S.-Mexico Migratory System

Abstract: We investigate the role of the Mexican government in assisting migrant workers in the labor claims-making process across three consular jurisdictions in the United States. Our analysis of administrative documents finds that consular support varies in relation to the local context within which consulates operate and depends on the circumstances of labor issues. We argue that binational claims, which involve migrants that have returned to Mexico, emerge in local economies characterized by cyclical migration of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…The Mexican consulate's Departamento de Protección is the key entity for deploying labor rights resources and outreach (often in conjunction with the Departamento de Asuntos Comunitarios). Drawing on data from three consulates (El Paso, Raleigh, and San Francisco), Martínez-Schuldt, Hagan, and Weissman (2021) found that consulates help workers throughout the labor claims process, provide a wide range of services (from general information to legal referrals to inhouse counsel), help broker interactions with various actors (including between migrants, with lawyers, and with other Mexican institutions), and can even be resources in the wake of an unsuccessful claim.…”
Section: Consular Labor Protection Servicesmentioning
confidence: 99%
“…The Mexican consulate's Departamento de Protección is the key entity for deploying labor rights resources and outreach (often in conjunction with the Departamento de Asuntos Comunitarios). Drawing on data from three consulates (El Paso, Raleigh, and San Francisco), Martínez-Schuldt, Hagan, and Weissman (2021) found that consulates help workers throughout the labor claims process, provide a wide range of services (from general information to legal referrals to inhouse counsel), help broker interactions with various actors (including between migrants, with lawyers, and with other Mexican institutions), and can even be resources in the wake of an unsuccessful claim.…”
Section: Consular Labor Protection Servicesmentioning
confidence: 99%